Graphene Nanoflake Antibody Conjugates for Multimodal Imaging of Tumors. Issue 9 (11th July 2021) - Lamb, Jennifer; Šimaitis, Joris; Halukeerthi, Siriney O.; Salzmann, Christoph G.; Holland, Jason P.
Abstract : Graphene‐based materials are promising scaffolds for use in the design of tailored‐made nanomedicines. Herein, the synthesis and characterization of a series of multifunctional carboxylated graphene nanoflakes (GNFs) conjugated to monoclonal antibodies (mAbs) for tumor‐specific binding and modulation of pharmacokinetics is presented. GNF–mAb constructs are coupled to a fluorophore (4, 4‐difluoro‐4‐bora‐3a, 4a‐diaza‐ s ‐indacene [BODIPY]) for applications in optical imaging, a paramagnetic Gd 3+ complex, [GdDOTAGA(H2 O)] −, and the hexadentate chelate desferrioxamine B (DFO) for radiolabeling with 89 Zr 4+ ( t 1/2 = 78.41 h) ions and applications in dual‐modality positron emission tomography/magnetic resonance imaging (PET/MRI). Experimental properties of [ 89 Zr]GdDOTAGA–ZrDFO–GNF–trastuzumab are tested in extensive chemical, spectroscopic, radiochemical, and cellular assays in vitro, and assessment of the pharmacokinetics by PET imaging in mice bearing a human ovarian cancer model illustrates the potential of using GNF–mAbs to develop multifunctional PET/MRI probes. Abstract : Pristine graphene nanoflakes with a carboxylated edge are functionalized with tumor‐specific antibodies and are used as scaffolds to develop multimodality agents for positron emission tomography/magnetic resonance imaging (PET/MRI). Antibody conjugation facilitates control over the tracer pharmacokinetics with increased circulation times, and enhanced drug delivery to the tumors.